Sturm-Liouville Problem for Stationary Differential Operator with Nonlocal Two-Point Boundary Conditions - Pečiulytė, S.; Štikonas, A. (Nonlinear Analysis: Modelling and Control, 2006)
The Sturm-Liouville problem with various types of two-point boundary conditions is considered in this paper. In the first part of the paper, we investigate the Sturm-Liouville problem in three cases of nonlocal two-point boundary conditions. We prove general properties of the eigenfunctions and eigenvalues for such a problem in the complex case. In the second part, we investigate the case of real eigenvalues. It is analyzed how the spectrum of these problems depends on the boundary condition parameters. Qualitative behavior of all eigenvalues subject to the nonlocal boundary condition parameters is described.